Peritoneal metastatic adenocarcinoma possibly due to a gastric duplication cyst: a case report and literature review - Liu, Kuiliang; Lin, Xiangchun; Wu, Jing; Liu, Hong; Meng, Mingming; Su, Hui; Tai, Weiping; Chang, Hong (BMC gastroenterology, 2014)
Gastric duplication cysts are rare congenital abnormalities, and malignant transformation of these duplications is also thought to be rare. During a routine health checkup, a 28-year-old man underwent abdominal sonography followed by computed tomography (CT) with contrast agent, which revealed a cystic lesion with no enhancement. Laparoscopic surgery showed a 10 × 10 cm cyst adhering to the gastric corpus. However, attempts to remove the lesion en bloc were unsuccessful, and the ruptured cyst had contaminated the peritoneal cavity. Gastric duplication was diagnosed from microscopic examination of the cyst. Seven months later, the patient suffered a progressive increase in ascites, and repeated cytological analysis showed small nests of adenocarcinoma cells, with primary lesion unknown. Diagnostic laparoscopy showed multiple white nodules scattered over the surface of the liver, greater omentum, and peritoneum. Biopsy of the omental nodules confirmed adenocarcinoma, while carcinomatosis was diagnosed in the peritoneum. Clinical presentation and chronological developments indicated that the malignancy probably originated from the gastric duplication cyst. This case highlights the importance of accurate preoperative diagnosis and optimal surgical management for gastric duplication as well as considering the potential existence of malignant transformation during surgical evaluation of adult patients with gastric duplication cysts.